PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP DIVIDEND POLICY DENGAN FREE CASH FLOW DAN INVESTMENT EFFICIENCY SEBAGAI VARIABEL MODERASI - Nindya Pangestika Pratiwi; Abdurrahman Abdurrahman (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2026)
This study aims to analyze the influence of ownership structure and board characteristics on dividend policy in companies listed in the Kompas 100 index during the 2018–2024 period with free cash flow and investment efficiency as moderation variable. The findings reveal that family ownership, institutional domestic ownership, ownership concentration, foreign ownership, managerial ownership, and the presence of independent commissioners have no significant impact on dividend policy. Conversely, board size and CEO duality show a positive and significant influence, while the presence of female directors has a negative and significant impact on dividend policy. Furthermore, the three tested moderating variables free cash flow and investment efficiency did not show significant effects in moderating the relationships between ownership structure or board characteristics and dividend policy.This study is limited by its long observation period, which spans pre-COVID, during the pandemic, and post-COVID recovery phases, leading to diverse dividend distribution patterns. Additionally, the use of moderating variables is still limited. Future researchers are encouraged to examine a more diverse set of companies and explore additional moderating variables to provide deeper insights. The managerial implications highlight the importance of board characteristics in maintaining long-term strategic stability while emphasizing the need for transparent and accountable reporting. For investors, the result can be used as a consideration in evaluating the company’s performance by paying attention to its development so that it grows into an increasingly larger company